Human Resource Information System in SU II Sub-district Palembang - Yulia, Indah Yulia; Abdillah, Leon Andretti (Sistemasi: Jurnal Sistem Informasi, 2024)
Advances in information technology and the internet make it very easy for a person to get information. Web-based information systems also play an important role in an organization, including Employee Promotion, Mutation, and Pension Information Systems in SU II District, Palembang City. The system was developed using the PHP programming language, MySQLi database, and Web Engineering methods. This web-based system can facilitate the General and Personnel Section in carrying out their duties and functions in processing data quickly with a responsive and user-friendly display so that it can be accessed on desktop and mobile devices and also it is equipped with a feature to send notifications to Email and WhatsApp. Another advantage of this web-based information system is equipped with a feature to send barcodes from important Decision Letters as a security measure in maintaining the confidentiality of important documents.